(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Some positive teaching outcomes for children with autism have been attributed to the effect of reinforcement for correct trained responses as well as to the effects of the consequences for incorrect responses, such as error-correction procedures. Some studies in error-correction procedures investigated the schedule of reinforcement used for correct responding. The goal of the present study was to compare a condition that provided reinforcers of the same magnitude for correct and independent responses with a second condition that provided reinforcers of different magnitudes for these responses. Rates of correct responses during tact and listener responding training were measured for three atypically developing children. The condition using different magnitudes of reinforcer resulted in fewer trials to establish tact repertoire for all participants, and to establish listening responding repertoire for two out of three participants.